Prosedur Dalam Penetapan Harga Produk Pada PT. Mirota KSM - Yusi Irensi Seppa (Indonesian Journal of Taxation and Accounting, 2023)
For every company that produces products, whether goods or services, it has a social goal and seeks profit and maintains the continuity of its business amidst competition. To achieve these company goals requires good coordination of all existing management functions. One thing that companies need to pay attention to in order to be able to compete amidst increasingly fierce business competition is good procedures in setting prices. Good and appropriate procedures for setting prices at PT Mirota KSM need to be carried out so that having appropriate pricing procedures can help the company to survive in the midst of market competition because price is a component that has a direct influence on the company's profit level. This research aims to determine the procedural steps in determining product prices at PT. Mirota KSM. The type of research used is qualitative research by describing phenomena and facts. Data was obtained from observations and interviews during industrial visit activities carried out. Based on research on procedures for determining product prices at PT. Mirota KSM can be concluded that there are six procedural steps for setting prices that can be taken into consideration by companies in developing policies in setting prices for their products, including: choosing a price target, determining demand, estimating costs, analyzing competitors' offers and prices, choosing a pricing method, and choose the final price.